PENGEMBANGAN BAHAN AJAR DIGITAL INSTALASI PENERANGAN LISTRIK BERBASIS CHALLENGE BASED LEARNING (CBL) UNTUK KEMANDIRIAN BELAJAR SISWA KELAS XI TEKNIK INSTALASI TENAGA LISTRIK - Perangin Angin, Bayu Andica; Mulyana, Dadang (JEVTE Journal of Electrical Vocational Teacher Education, 2023)
Abstract The objectives to be achieved in this research are to find out: (1) Development of digital teaching materials using the Challenge Based Learning learning model as a learning medium. (2) The feasibility and effectiveness of student learning using digital teaching materials. The Challenge Based Learning Model. Research was carried out at the Imelda Private Vocational School, Medan. This research uses research and development methods or better known as Research and Development (R&D). This product development model is a series of procedures to produce learning media for Challenge Based Learning-based learning media applications on understanding Electrical Installation Concepts for secondary vocational students XI Electrical Power Installation. This product development model uses the ADDIE Lee and Owens model. The results of the research show that: The digital teaching materials with the flipbook maker-based Challenge Based Learning learning model that the researchers developed are suitable for use in the learning process. The results obtained from the assessment are: (1) Assessment of digital teaching material and media using the Challenge Based Learning learning model based on the flipbook maker that researchers developed for the "Material" aspect, an assessment score of 89.50% was obtained in the "Very feasible" category and for the "Media" aspect of 86.25% in the "Very feasible" category. (2) Obtaining digital teaching materials using the flipbook maker-based Challenge Based Learning learning model that researchers developed obtained an effectiveness percentage of 80.6% with very effective criteria, and can be used as a model to support learning activities. The content feasibility aspect score is 89.50% and is included in the "Very feasible" criteria. Key Words: Digital teaching materials, challenge based learning, single phase electric lighting installation.AbstrakTujuan yang akan dicapai dalam penelitian ini yaitu untuk mengetahui: (1) Pengembangan bahan ajar digital dengan model pembelajaran Challenge Based Learning sebagai media pembelajaran. (2) Kelayakan dan keefektifan belajar siswa dengan menggunakan bahan ajar digital Model Challenge Based Learning Penelitian dilaksanakan di SMK Swasta Imelda Medan. Penelitian ini menggunakan metode penelitian dan pengembangan atau lebih dikenal dengan Research and Development (R&D). Model pengembangan produk ini adalah serangkaian prosedur rangka menghasilkan media pembelajaran aplikasi media pembelajaran learning berbasis Challenge Based Learning pada pemahaman Konsep Instalasi Listrik untuk siswa menengah kejuruan XI Instalasi Tenaga Listrik. Model pengembangan produk ini menggunakan model ADDIE Lee dan Owens. Hasil penelitian menunjukkan bahwa: Bahan ajar digital dengan model pembelajaran Challenge Based Learning berbasis flipbook maker yang peneliti kembangkan sudah layak digunakan dalam proses pembelajaran, didapatkan hasil dari perolehan penilaian yaitu: (1) Penilaian materi dan media bahan ajar digital dengan model pembelajaran Challenge Based Learning berbasis flipbook maker yang peneliti kembangkan untuk aspek œMateri diperoleh skor penilaian sebesar 89,50% dengan kategori œSangat layak dan aspek œMedia sebesar 86,25% dengan kategori œSangat layak. (2) Perolehan bahan ajar digital dengan model pembelajaran Challenge Based Learning berbasis flipbook maker yang peneliti kembangkan diperoleh persentase efektifitas sebesar 80,6% dengan kriteria sangat efektif, dan dapat digunakan sebagai model dalam mendukung kegiatan pembelajaran. Skor aspek kelayakan isi sebesar 89,50% dan termasuk dalam kriteria œSangat layakKata kunci : Bahan ajar digital, challenge based learning, instalasi penerangan listrik satu fasa